Неоіндустріальний розвиток металургії України: передумови, проблеми, напрями - Нікіфорова, В.А. (Економіка промисловості, 2016)
У результаті аналізу ключових тенденцій світового виробництва та споживання металопродукції виявлено ключові напрями неоіндустріалізації металургії у зарубіжних країнах, які є цілком актуальними для реалізації в Україні. Досліджено тенденції, особливості та результати діяльності металургійної промисловості України в цілому та Донбасу зокрема у 2013-2015 рр. у контексті військових дій на сході країни. З урахуванням особливостей розвитку галузі визначено стратегічні напрями неоіндустріалізації металургії України, запропоновано напрями впровадження відповідної державної галузевої політики. В результате анализа ключевых тенденций мирового производства и потребления металлопродукции выявлены основные направления неоиндустриализации металлургии в зарубежных странах, которые вполне актуальны для реализации в Украине. Исследованы тенденции, особенности и результаты деятельности металлургической промышленности Украины в целом и Донбасса в частности в 2013-2015 гг. в контексте военных действий на востоке страны. С учетом особенностей развития отрасли определены стратегические направления неоиндустриализации металлургии Украины, предложены направления внедрения соответствующей государственной отраслевой политики. The key trends in the world production and consumption of steel are analyzed. It has been revealed that in the period from 1970 to 2015 an unprecedented growth in the volume of metal production was observed, in which the steel production increased by 2,7 times. The geographical pattern of production and consumption of steel changed crucially. There was a shift of "centers" of metals trade and smelting to the rapidly developing countries of Asia, North Africa, and South America. Metal overproduction and change in its geographic production structure have led to an aggravation of supply, environmental and resource issues in the global steel industry. These trends are the prerequisites for alterations of industrial policy in most countries, dubbed "neoindustrialization". In the article the main directions of neoindustrialization of metallurgy in foreign countries are identified, which is quite relevant for implementation in Ukraine. The trends, features and results of performance of the Ukrainian steel industry as a whole and the Donbass one in particular in 2013-2015 in the context of military operations in the East of the country have been researched in details. It has been revealed that neoindustrial model for the metallurgy in Ukraine should take into account the specific differences of development, and above all, the availability of economic and political factors blocks of the branch activities at the present stage.The characteristics of the industry are given, strategic directions of neoindustrialization of Ukrainian metallurgy are identified, and the introduction of the corresponding directions of the state industrial policy is proposed. Today there is an urgent need for the elaboration and adoption of two basic regulatory documents that will directly or indirectly govern the development of the steel industry at neoindustrial basis: the long-term nationwide strategy for the development of domestic steel industry and the strategy of revival of the territory of Donbass, which is temporarily not controlled by Ukraine.Solution of problems and further development of the metallurgy of Donbass in particular and in Ukraine as a whole are also seen in the modernization of production using the new industrial base. At the same time, the recovery of Donbass should be considered as one of the main points of the growth of the entire Ukrainian economy and its steel industry.